(untitled) (Economic and Political Thought, 2017)
In December 1991 the Union of Soviet Socialist Republics broke up. Researchers of this problem have classified factors that led to the break-up of the USSR. There are several groups of such causes: ideological, political, social, economic, nomenclature or national ones. The essence of this article will be the presentation of the emancipation of the Soviet nomenclature at various stages of the history of the USSR till the final stage of this process – the disintegration of the Soviet empire. The emancipation of the nomenclature was one of the manifestations of the multi-faceted modernization of the USSR and its collision with the communist doctrine as an ideology. Various attempts to reform the Soviet Union, marking epochs in its history, confirmed the utopian character of Soviet communism in the ideological dimension. The failed reforms of the communist system contributed to the emergence of various interest groups within the growing Soviet nomenclature. These groups were fiercely competing for power, and in that situation the maintenance of the nomenclature consensus, which bound the Soviet empire, became very difficult. The last attempt to reform communism and the USSR – perestroika – weakened the central authority enough to lead to the strengthening of particularism of the nomenclature. As a result of this complex process, a large of the Soviet nomenclature gained independence from the centre, and by entering into alliances or by concessioning national and democratic movements in union republics, it gained democratic legitimacy and joined the disassembly of the Soviet Union.